2023
DOI: 10.1038/s41598-023-37714-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a 21-gene prognostic signature in neuroblastoma

Abstract: Survival outcomes for patients with neuroblastoma vary markedly and reliable prognostic markers and risk stratification tools are lacking. We sought to identify and validate a transcriptomic signature capable of predicting risk of mortality in patients with neuroblastoma. The TARGET NBL dataset (n = 243) was used to develop the model and two independent cohorts, E-MTAB-179 (n = 478) and GSE85047 (n = 240) were used as validation sets. EFS was the primary outcome and OS was the secondary outcome of interest for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Various prognostic signatures for NB have been reported in previous studies ( 12 , 46 , 47 ). However, to our knowledge, no previous study in NB has reported measuring stemness for prognostication.…”
Section: Discussionmentioning
confidence: 94%
“…Various prognostic signatures for NB have been reported in previous studies ( 12 , 46 , 47 ). However, to our knowledge, no previous study in NB has reported measuring stemness for prognostication.…”
Section: Discussionmentioning
confidence: 94%
“…2 Studies increasingly report the connection of molecular profiling results with thyroid tumor biology and outcomes, 3,4 offering important prognostic information from a fine-needle biopsy alone and, thus, perfectly suited to improve patient selection for nonoperative strategies. The use of molecular profiling for prognosis is common in other cancers 5,6 and its application routinely guides clinical care of breast cancer 7 -why should thyroid cancer care lag behind?…”
mentioning
confidence: 99%